Vitamin E supplementation and endurance exercise: are there benefits? - Takanami, Y.; Iwane, H.; Kawai, Y.; Shimomitsu, T. (Sports Medicine, 2000)
It has been widely noted that vitamin E shows numerous beneficial effects through and beyond its antioxidative properties; consequently, vitamin E is expected to prevent degenerative diseases. In the field of sports medicine, many studies dealing with vitamin E have been conducted originally from the point of view of its effects on physical performance. Although some earlier studies indicated that vitamin E supplementation could improve physical performance, defects in the study design or statistical analysis were pointed out at a later time. The majority of subsequent well controlled studies have reported no significant effect on physical performance from vitamin E supplementation. Recent studies suggest that endurance exercise may promote free radical generation in the body, and vitamin E may play an important role in preventing the free radical damage associated with endurance exercise. Although there is evidence of free radical involvement in exercise-induced muscle injury, vitamin E supplementation might not be expected to prevent muscle damage caused by exercise in humans without a vitamin E deficiency. Since it is still unclear whether exercise induces lipid peroxidation in the human body, the beneficial effect of vitamin E supplementation on exercise-induced lipid peroxidation has not yet been established. However, it is proposed that as a result of exercise vitamin E may be mobilised from store tissues and redistributed in the body to prevent oxidative damage. Therefore, we are convinced that vitamin E contributes to preventing exercise-induced lipid peroxidation. It has also been indicated that strenuous endurance exercise may enhance the production of oxidised low density lipoprotein (LDL), which plays a key role in the initiation and progression of atherosclerosis. It is also suggested that this enhanced production of oxidised LDL could be reduced if a higher vitamin E status is maintained. Supplementation with 100 to 200mg of vitamin E daily can be recommended for all endurance athletes to prevent exercise-induced oxidative damage and to reap the full health benefits of exercise.